Synthesis of novel three-dimensional flower-like cerium vanadate anchored on graphitic carbon nitride as an efficient electrocatalyst for real-time monitoring of mesalazine in biological and water samples - Kanna Sharma, Tata Sanjay; Hwa, Kuo-Yuan; Santhan, Aravindan; Ganguly, Anindita (Sensors and actuators. B, Chemical, 2021)
•g-C3N4/CeVO4/SPC electrode is used to determine anti-inflammatory mesalazine drug.•The g-C3N4/CeVO4/SPCE has shown a good sensitivity of 18.92 μA μM−1 cm−2.•A wide working range of 0.002−380 μM and LOD of 0.00547 μM is exhibited using DPV.•Real-time analysis is carried in biological and pharmaceutical samples. Rare-earth metal vanadate has gained much interest in recent years due to its excellent catalytic properties and chemical stability in electrochemical sensors. In this study, we have explored the electrochemical activity of graphitic-carbon nitride (g-C3N4) and hierarchical 3D cerium vanadate (CeVO4) by using screen printed carbon paste electrode (SPCE) for detection of mesalazine (MEZ). Successfully, g-C3N4 and CeVO4 were synthesized by using a simple hydrothermal process, and then to form a nanocomposite ultrasonication procedure is approached. To confirm the structural and morphological parameters X-ray diffraction (XRD), X-ray photoelectron spectroscopy, Field-emission scanning electron microscopy (FE-SEM), Transmission electron microscopy (TEM) is being utilized. The g-C3N4/CeVO4/SPCE modified electrode has exhibited superior electrocatalytic performance in detecting MEZ with lower Rct value and with the high active surface area when compared with other electrodes. The prepared sensor has shown good sensitivity 18.92 μA μM−1 cm−2 and with a huge working range of 0.002−380 μM, with a promising trace-level limit of detection of about 0.00547 μM by using differential pulse voltammetry (DPV). Henceforth, g-C3N4/CeVO4/SPCE was carried out to subject real-time application in detecting MEZ in various biological, river water, and pharmaceutical samples which resulted in excellent recovery stating the chosen sensor is applicable in real-time analysis.